Representasi Diri Terhadap Lingkungan Sekitar Dalam Seni Grafis Teknik Cetak Tinggi - Muhammad dava Ganindra; Joko Lulut Amboro (VisArt: Jurnal Seni Rupa dan Design, 2026)
This art creation article discusses self-representation toward the surrounding environment in relief printmaking. The main issue is how personal experience, social interaction, and the search for identity are visualized through the visual character of relief printing. The concept is derived from the artist’s experiences within campus life, family, friendship, career orientation, and love. The method applies an art creation process consisting of exploration, design, embodiment, and evaluation. Exploration was conducted through personal observation, literature review, and analysis of relevant artworks. Design included sketching, symbolic arrangement, and compositional selection. The embodiment stage was carried out through linocut on lino rubber and printed on linen paper. The results show that relief printmaking can express personal experience through strong lines, carved textures, contrast, and figurative forms. The works serve not only as personal expression but also as a reflective medium about the relationship between individuals and their social environment